Analysis Factors of Environmental Carrying Capabilities that Affect the Highness of Tourism Visits in the Form of Interest, Initiation, Loyalty with Structural Equation Modelling (SEM) - Arie Wahyu Prananta; Agustinus Gergorius Raja Dasion; Firmansyah Firmansyah; Durrotul Farihah (Jurnal Penelitian Pendidikan IPA, 2023)
The environmental carrying capacity in coastal areas is interesting to develop and can be achieved through two approaches, namely the supply side approach and the demand side approach. From the supply side, this research aims to implement the Carrying Capacity of the Coastal Environment, this research seeks to understand the relationship between external factors in the form of Interest, Initiation, Loyalty, Content Validity has been used with the Content Validity Index (CVI) method, while Construction Validity has been used with the Confirmatory method Factor Analysis used Amos 23. The scale validation subjects involved 308 respondents. The research results show that 16 items measure Interest, Initiation, and Loyalty. The modification results show that the model fits with 16 statements containing the factors Interest, Initiation, and Loyalty, as indicated by the Chi-Square values which are not significant, GFI (0.99), CFI (0.91).